The Influence of Social Media Promotion, Online Customer Reviews, and Brand Image on Purchasing Decisions for Fashion Products Online at Marketplace Shopee (Study on the General Public of Purwokerto City) - Rifai, Fredi Maulana Rifai; Rachmawati, Erny; Widyaningtyas, Dian; Purnadi, Purnadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The study had the purpose to test and do an analysis on the effect of social media promotions, online customer reviews, as well as brand image on purchasing decisions for online fashion products in Shopee. Quantitative was used as the research methods, with the focus on people who live in Purwokerto. Respondents used in this research sample were 113 according to the criteria involved in purchasing decisions for online fashion products in Shopee. The method for collecting data is through a questionnaire distribution survey, which is measured on a 5-point Likert scale and then analyzed through the utilization of SPSS 26 application. The findings revealed that social media promotion, along with brand image, affect purchasing decisions positively and significantly for online fashion products in the marketplace Shopee. Whereas, online customer reviews show an effect that is negative and insignificant on purchasing decisions for online fashion products in Shopee.